Perspektif Mahasiswa terhadap Metode, Media, dan Model Pembelajaran Daring Setelah Pandemi Covid-19 - Miftah Arifin; Anas Ma'ruf Annizar; Ari Faizatisyam Putra Nusantara (SAP (Susunan Artikel Pendidikan), 2023)
As a result of the COVID-19 pandemic, there have been significant changes in the world of education, from offline learning to online learning. They have always been an exciting topic to discuss to find the most effective and efficient learning solutions for educators and students, including at the university level. For this reason, this research was conducted to explain the method of delivering material, platforms/social media, learning models that are easy and effective for students, and perceived barriers to online learning. The method used in this research is a survey method with a quantitative approach. The population is all students at Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, with the determination of the sample using the Slovin method. The results obtained showed that 57.7% the delivery of the material was more effective and efficient if it was done with live video (video conference), with a platform that was considered easy and effective was Google Meet, while the obstacle felt by 63% of the sample in online learning was the internet network. Thus, inadequate internet network was found to disturbed the concentration. Furthermore, Blended Learning was the learning model that students want to apply.